Pemberdayaan Masyarakat Revolusi Mental Melalui Gerakan Literasi Sekolah - Amaliati, Siti; Maani, Arifatul; Anggraeni, Desi; Fajriani, Adinda Nurul; Widadi, Nurul; Farthonia, Romy Thoriq; Zainullah, Muhammad Haris; Masitho, Dewi (Journal of Community Sustainability, 2024)
The community service activity titled "Mental Revolution Through School Literacy Movement" aims to enhance the literacy culture among elementary school students. This program employs an action research approach consisting of four main stages: planning, action, observation, evaluation, and reflection. Through a series of activities such as independent reading, group discussions, and book reviews, students are encouraged to understand the importance of literacy in everyday life. The results of this activity indicate an increase in students' motivation to read, as well as the development of critical thinking and communication skills. The symbolic awards given to students who show high enthusiasm contribute to a positive competitive atmosphere, encouraging other students to participate more actively. The reflection conducted at the end of the activity shows that students feel more confident and motivated to read more, indicating the program's success in fostering positive reading habits. Additionally, the integration of literacy with character education proves to be essential in shaping students' resilient mentality. This program not only successfully instills reading habits but also demonstrates the crucial role of educational institutions in building a literacy culture in society, which in turn contributes to the development of superior and competitive human resources in the future.